Kondisi dan pola pemanfaatan siput gonggong di Perairan Pulau Penyengat Kecamatan Tanjungpinang Kota, Kepulauan Riau, Indonesia - Raja Wira Pradana; Febrianti Lestari; Susiana (Sekolah Tinggi Ilmu Pertanian Wuna, 2020)
This study aims to determine the conditions and patterns of utilization of snails in the Penyengat island waters, Riau Island, Indonesia. The method used was purposive sampling of 5 stations with 70 x 2 m quadratic transect for the density of the Gonggong Snail. The results found two types of snail bark species namely Laevistrombus turturella and Strombus urceus with a total density value of 0.114individual per m². The use of snail bark patterns in Penyengat Island waters, namely the size of the catch is medium to large, manual capture techniques (collected by hand), the catching area in the waters of the island is 100-200 m from the beach, the most catches found >100 individuals, season and time of catching snail barks at stinging island waters are not based on season, utilization and distribution of utilization. The snail bark resource is used for consumption and sold to collectors.